2019
DOI: 10.1007/978-3-030-17219-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Complexity in Science|Environment|Health Pedagogy

Abstract: This paper aims to discuss complexity as a key feature for understanding the role of science knowledge in environmental and health contexts -a core issue in Science|Environment|Health pedagogy. Complex systems are, in principle, not predictable. In different contexts, ephemeral mechanisms produce different, sometimes completely unexpected results. The "art of decision making" in complex contexts is to take scientific knowledge into account, but to interpret its meaning in terms of concrete complex contexts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Science-Environment-Health pedagogy necessarily deals with complex systems in which students have to develop the "art of decision making" [64]. Along this paper we have been working with global and interrelated concepts under construction and in continuous evolution, building a multifaceted model dealing with aspects such as hunger or overconsumption, considered as part of social sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Science-Environment-Health pedagogy necessarily deals with complex systems in which students have to develop the "art of decision making" [64]. Along this paper we have been working with global and interrelated concepts under construction and in continuous evolution, building a multifaceted model dealing with aspects such as hunger or overconsumption, considered as part of social sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…In the S|E|H movement, complexity has become a core issue [29,30]. Living organisms are non-linear, self-organizing systems that are involved in open exchanges of energy and matter with the environment.…”
Section: Science|environment|healthmentioning
confidence: 99%
“…Other studies, however, point to the exact opposite (e.g., [54,55]). Reasons for this inconsistency can be found in the subject matter and its complexity, as well as in the process of human decision-making [56].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The proposed three-dimensionality has been tested, and it was shown that health knowledge concerning the reduction of sugar consumption in favor of type 2 diabetes prevention could be treated as three-dimensional, hence consisting of SK, AK, and EK [56]. Since this three-dimensionality of health knowledge was derived from theory and adopted in a model for decision-making [23], it needs validation.…”
mentioning
confidence: 99%